Towards achieving a large-area and defect-free nano-line pattern via controlled self-assembly by sequential annealing. (December 2021) - Wen, Tao; Ni, Bo; Liu, Yuchu; Zhang, Wei; Guo, Zi-Hao; Lee, Yi-Chien; Ho, Rong-Ming; Cheng, Stephen Z.D.
Abstract: Utilizing the controlled self-assembling of a giant surfactant, a bottom-up method for constructing line gratings with sub-10 nm resolution has been developed. Via a simple solvent vapor annealing procedure, the giant surfactant comprised of an oligomeric silsesquioxane (DPOSS) and polystyrene (PS) tail ( i.e., DPOSS-PS) has been precisely self-assembled into perpendicularly oriented lamellae structures. A follow-up thermal annealing further significantly promotes the long-range ordering, giving rise to highly oriented and defect-free sub-10 nm line patterns (up to areas of several µm 2 ). The solvent evaporation and thermal annealing process, together with the strong segregation strength ( χN ) of DPOSS-PS, play crucial roles in the self-orientation and width-reduction of the line patterns. This simple processing of the easy-accessed giant surfactants results in a facile and more economic approach for large-scale nano-sized line grating fabrication. Graphical abstract: Image, graphical abstract